Biskupa Zdzisława Golińskiego koncepcja Archiwum Diecezjalnego w Częstochowie - Wolnicki, Paweł (Archiwa, Biblioteki i Muzea Kościelne, 2011)
Bishop prof. dr hab. Z. Goliński’s legacy, preserved in the Archive of Metropolitan Curia in Częstochowa, revealed the sphere of his influence hitherto unknown. As a professor of moral theology, he felt responsible for the archive material relating to the past of the Diocese of Częstochowa. He was involved in collecting material concerning the history of the mentioned diocese. He also valued the latest documentation produced by the Diocesan Curia in Częstochowa. In his opinion it should not only be collected but also properly organized. Bishop Goliński learnt the respect for the archive material in his family and that is why he paid so much attention to the way this material was kept. He created the department for archive and entrusted it with the coordination of the archival tasks. He also built the necessary plan of the records of the Curia Archive and the relevant archival regulations for the Church of Częstochowa. The Bishop controlled this area personally with the help of the Chancellor issuing orders which were to improve archival activities of the Curia and Diocese. He had his concept of the archive for a Particular Church, based probably on the family experiences and the practice in running the personal archive. Bishop prof. dr hab. Zdzisław Goliński certainly stood out from the members of the Polish episcopate. He paid a great deal of attention to the competence of people employed in church archives and to the role of these structures in Curia and the whole Particular Church.